Cost-effectiveness of a pentavalent rotavirus vaccine in Japan. (October 2013) - Itzler, Robbin; O'Brien, Megan A.; Yamabe, Kaoru; Abe, Machiko; Dhankhar, Praveen
Abstract Objective: To evaluate the impact of universal vaccination with a pentavalent rotavirus vaccine (RV5) on the healthcare burden and costs associated with rotavirus gastroenteritis (RGE) in Japan. Methods: The model included a hypothetical cohort of 1, 091, 156 children followed for their first 5 years of life. In the absence of universal vaccination, there were 19 deaths, 78, 000 hospitalizations, and 678, 000 outpatient visits due to RGE. The efficacy of RV5 is based on international clinical trial data, which was similar to the efficacy observed in clinical trials conducted in Japan. The primary outcome measure is the cost per quality-adjusted-life-year (QALY) gained. In the base case, the QALY loss per 1000 RGE episodes included 2.2 for children and 1.8 per parent. Results: Universal vaccination is projected to reduce hospitalizations by 92%, outpatient visits by 74%, and work-loss days by 73%. For the base case analysis, the total vaccination cost was ¥26 billion. The estimated reduction in medical costs was ¥16 billion. Of 2500 QALYs gained with the vaccination program, approximately half are directly attributed to the child. In the base case analysis, the incremental cost-effectiveness ratio (ICER) for vaccination vs no vaccination is ¥4 million and ¥2 million per quality-adjusted life year (QALY) gained from the healthcare payer and societal perspectives, respectively. The ICERs are ¥8 million and ¥4 million if parental disutilities are excluded. Key limitation: The QALY decrements for children and parents were evaluated using different instruments, and the QALY decrements do not vary based on episode severity. Given the interdependence between children and their parents, excluding parental disutilities may under-estimate the impact of RGE. Conclusion: Universal vaccination with RV5 in Japan is projected to have a substantial public health impact and may be cost-effective from both the payer and societal perspectives if parental disutilities are included in the cost-effectiveness ratios.